Vibrational coherent control of localized d–d electronic excitation - Marciniak, Alexandre; Marcantoni, Stefano; Giusti, Francesca; Glerean, Filippo; Sparapassi, Giorgia; Nova, Tobia; Cartella, Andrea; Latini, Simone; Valiera, Francesco; Rubio, Angel; Van Den Brink, Jeroen; Benatti, Fabio; et al. (Nature Physics, 2021)
Addressing the role of quantum coherence in the interplay between the different matter constituents (electrons, phonons and spin) is a critical step towards understanding transition metal oxides and designing complex materials with new functionalities. Here we use coherent vibrational control of on-site d–d electronic transitions in a model edge-sharing insulating transition metal oxide (CuGeO3) to single out the effects of vibrational coherence in electron–phonon coupling. By comparing time-domain experiments based on high- and low-photon-energy ultrashort laser excitation pulses with a fully quantum description of phonon-assisted absorption, we could distinguish the processes associated with incoherent thermal lattice fluctuations from those driven by the coherent motion of the atoms. In particular, while thermal fluctuations of the phonon bath uniformly increase the electronic absorption, the resonant excitation of phonon modes also results in light-induced transparency that is coherently controlled by the vibrational motion.
CRIS-Team Scopus Importer:2022-07-20